2020
DOI: 10.1039/d0ra06697d
|View full text |Cite
|
Sign up to set email alerts
|

A study on the selective catalytic reduction of NOx by ammonia on sulphated iron-based catalysts

Abstract: The roles of Fe3+ and SO42− are different at low and high temperatures due to their interaction. It is the appropriate contents of Fe3+ and SO42− that can result in high NH3-SCR activity at varying temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…A very promising NO conversion efficiency at 350 • C for Fe-CLIN catalysts (above 85%) was observed (Figure 7a). This behavior was also reported by literature [29,54] for CATCO (approximately 91%) in the presence of water. However, in the presence of SO 2 both FeMORD and CATCO catalysts show a NO conversion efficiency above 91%.…”
Section: Activity Testssupporting
confidence: 89%
See 1 more Smart Citation
“…A very promising NO conversion efficiency at 350 • C for Fe-CLIN catalysts (above 85%) was observed (Figure 7a). This behavior was also reported by literature [29,54] for CATCO (approximately 91%) in the presence of water. However, in the presence of SO 2 both FeMORD and CATCO catalysts show a NO conversion efficiency above 91%.…”
Section: Activity Testssupporting
confidence: 89%
“…SO 2 adsorption is competitive with NH 3 adsorption at Lewis acid sites and occurs rapidly and irreversibly at low temperatures. Sulfur dioxide reacts with surface ions producing sulfite and sulfate species at temperatures between 200 and 350 • C. Above 350 • C in the presence of oxygen, only sulfate species are formed on the surface, whereas sulfur trioxide (SO 3 ) is adsorbed at higher temperatures, which can lead to a reduction in the activity of catalysts in the presence of SO 2 [53][54][55].…”
Section: Activity Testsmentioning
confidence: 99%
“…This indicates that more Fe species are present in higher valence state on Fe-Zr catalyst, corresponding to higher content of Zr 3+ species. Moreover, recently on functionalized iron hydroxyapatite catalysts it was clearly shown that the presence of Fe 3+ highly dispersed on the surface led to a high selectivity to N 2 , a satisfactory activity in a wide temperature window [41] and improved catalytic activity [34]. Figure 4A,B presents catalytic results of Cu-Zr catalyst.…”
Section: Surface Properties Of Zro 2 Supported Catalystsmentioning
confidence: 93%
“…The activities of sulphate Fe-based catalysts improved significantly compared to the Fe/Zr catalyst, when tested in the temperature range of 250-500 • C. The authors showed that sulphate supplied higher number of acid sites, which could adsorb more NH 3 species that can react with gaseous NO + O 2 . Recently, Liu et al [34] investigated the selective catalytic reduction of NOx with ammonia over sulphated iron-based catalysts in using different loadings of Fe 3+ and SO 4 2− on zirconia support. Their results indicated that the interaction between Fe 3+ and SO 4 2− can have an effect on the redox ability, acid sites, and adsorption of NOx and NH 3 .…”
Section: Introductionmentioning
confidence: 99%